QUALITY INDICATORS OF BICOMPONENT YARN MADE FROM NATURAL FIBERS WITH HIGH HYGIENIC PROPERTIES - Davronov Bakhromjon Vakhobjon o‘g‘li (Web of Journals Publishing, 2025)
In this article, based on the analysis of modern researches devoted to the process of weaving fabric made from natural and cotton raw materials, information and recommendations were given about the working process of the currently used equipment, sorting equipment of theoretical and practical importance. The task and purpose of the research is to increase the efficiency of weaving, reduce the cost of weaving and prepare a competitive product in the world market by conducting theoretical and practical research. This product is made of 100% natural fibers.
Keywords: Cocoons, natural silk, raw silk, unwinding, warping, twisting, surgical thread, resulting linear density, quality, standard, surgical operation.